Septin-3 autoimmunity in patients with paraneoplastic cerebellar ataxia - Miske, Ramona; Scharf, Madeleine; Borowski, Kathrin; Rieckhoff, Nicole; Teegen, Bianca; Denno, Yvonne; Probst, Christian; Guthke, Kersten; Didrihsone, Ieva; Wildemann, Brigitte; Ruprecht, Klemens; Komorowski, Lars; et al. (Journal of neuroinflammation, 2023)
Septins are cytoskeletal proteins with filament forming capabilities, which have multiple roles during cell division, cellular polarization, morphogenesis, and membrane trafficking. Autoantibodies against septin-5 are associated with non-paraneoplastic cerebellar ataxia, and autoantibodies against septin-7 with encephalopathy with prominent neuropsychiatric features. Here, we report on newly identified autoantibodies against septin-3 in patients with paraneoplastic cerebellar ataxia. We also propose a strategy for anti-septin autoantibody determination.
Gesehen am 13.06.2023